2019
DOI: 10.1590/fst.16918
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ultrasound-assisted extraction of bioactive compounds from jabuticaba (Myrciaria cauliflora) fruit through a Box-Behnken experimental design

Abstract: Jabuticaba is a very popular fruit in Brazil being a great source of compounds with considerable biological activities. Novel optimized ultrasound-assisted extraction (UAE) methods have been proposed for anthocyanins and total phenolic compounds from jabuticaba. A Box-Behnken experimental design (BBD) with a response surface methodology (RSM) was used to investigate the effect of six independent variables (solvent composition, solvent-to-sample ratio, ultrasound amplitude and cycle, pH, and temperature) on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 59 publications
2
14
0
1
Order By: Relevance
“…Therefore, low agreement between experimental and predicted values for phenolic compounds was obtained by using the second-order polynomial equation. This value of lack of adjustment is expected and other authors have obtained similar results [35]. Phenolic compounds are a very wide family of compounds that encompass molecules of many polarities and sizes, from simple phenolic compounds to tannins.…”
Section: Experimental Design Of the Extraction Methods For Total Phenosupporting
confidence: 82%
“…Therefore, low agreement between experimental and predicted values for phenolic compounds was obtained by using the second-order polynomial equation. This value of lack of adjustment is expected and other authors have obtained similar results [35]. Phenolic compounds are a very wide family of compounds that encompass molecules of many polarities and sizes, from simple phenolic compounds to tannins.…”
Section: Experimental Design Of the Extraction Methods For Total Phenosupporting
confidence: 82%
“…The variability between the nature of the bioactive compounds, especially the wide range of polarity, makes that in this type of designs the lack-of-fit test usually appears in this range. In any case, the optimal conditions obtained are a compromise situation to extract the most desirable quantity of these compounds [ 31 ]. Furthermore, based on these results, it can be confirmed that the analysis explains 85.01% of the total variability, which is consistent with the statistical similarity between the experimental and predicted values.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, studies have shown that slow pasteurization leads to reduced levels of some of the antioxidant components present in HM such as glutathione peroxidase (Silvestre et al, 2008), vitamin C (Moltó-Puigmartí et al, 2011, total antioxidant capacity (Nogueira et al, 2018;Silvestre et al, 2008) In this context, innovative methods of food preservation such as ultrasound (US), high pressure, ionizing radiation, pulsed electric field, microfiltration and ultraviolet radiation, have been tested as possible alternatives to conventional thermal treatments in order to maintain microbiological safety with less impact on nutritional, functional and sensory aspects (Monteiro et al, 2020;Shabbir et al, 2020;Jasmi et al, 2020;Awad et al, 2012). In this context, the treatment of food with ultrasound (US) can offer an alternative to traditional methods (Piñon et al, 2019;Fernández-Barbero et al, 2019). This technology is considered a non-thermal emerging technology and has been extensively investigated for food processing in order to avoid the negative effects of conventional heat treatment (Bastos et al, 2019;Guimarães et al, 2019).…”
Section: Impact Of Ultrasound Treatment On Viability Of Staphylococcus Aureus and The Human Milk Antioxidant Activitymentioning
confidence: 99%